Changes in Adolescent Meal Patterns and Processed Food Consumption Following Sleep Restriction: Results From a Randomized Crossover Trial. (7th June 2021) - Whitacre, Catharine; Duraccio, Kara; Summer, Suzanne; Nommsen-Rivers, Laurie; Beebe, Dean
Abstract: Objectives: To evaluate if sleep restriction influences 1 ) meal frequency and late evening food consumption; and 2 ) intake of ultra-processed foods in male and female adolescents. Methods: A total of 92 healthy adolescents 14–17 years old participated in a cross-over experimental sleep protocol, comparing two conditions, each lasting 5 nights: healthy sleep (HS, 9.5 h/night) and shortened sleep (SS, 6.5 h/night). The order of conditions was randomly counterbalanced, and there was a washout period of 2 days between conditions. The study team conducted 24-h dietary recalls on 3 randomly selected days during each sleep condition. For objective 1, we used the timestamps of the meals in each dietary recall to determine number of eating occasion in 24 h, number of eating occasion after 8PM, and kilocalories consumed after 8PM. For objective 2, we used the Nova food classification system to determine kilocalories and % of kilocalories consumed from ultra-processed foods (UPF) over 24 hours and after 8PM. We used general linear model analysis to compare these outcomes between HS and SS conditions. We also explored the moderating impact of individual and experimental factors, including family income and participant age, sex, age- and sex-adjusted body mass index, and the order in which they had the sleep conditions. Results: There was no significant difference in number of eating occasions in 24 h across experimental conditions (SS = 4.2, HS = 4.1, P = .25). After 8PM, there was a significantly greater number of eating occasions (0.87 vs. 0.59, P < .001) and higher kilocalorie consumption (354 vs. 223, P < .001) during SS than HS. There was no difference in daily UPF kilocalorie consumption across conditions (SS = 1439, HS = 1397, P = .38), but UPF kilocalories after 8PM were significantly higher during SS than HS (291 vs. 172, P < .001). These findings did not vary based on our exploratory individual and experimental factors. Conclusions: Adolescents who are sleep restricted are more likely to eat more frequently, consume greater kilocalories, and eat highly processed foods after 8PM. Considering that these findings were not observed across the entire day, our findings suggest that sleep restriction may most negatively influence dietary patterns in the late evening. Funding Sources: NIH.